GAGASAN K.H. AHMAD DAHLAN TENTANG PENDIDIKAN ISLAM YANG IDEAL DAN RELEVANSINYA DENGAN KEBIJAKAN MERDEKA BELAJAR - ahmad Abimubarok (Universitas Muhammadiyah Tangerang, 2022)
ABSTACT The ideal Islamic education according to K.H. Ahmad Dahlan needs to be re-examined based on its relevance to the merdeka belajar policy. This was done as an effort to reconstruct the educational idea of K.H. Ahmad Dahlan who became the main motor, especially education in Muhammadiyah. This research uses a qualitative approach using qualitative descriptive method. The results of the study illustrate that reason, charity, and progress are the ideas of K.H, Ahmad Dahlan regarding the ideal Islamic education. These three ideas seem relevant to the merdeka belajar policy promoted by the Ministry of Education and Culture. Component reason is what shapes students to have high-level reasoning. Charity is a component that makes up the contribution of education to society. Progress is a component that makes schools must continue to improve themselves in order to be able to adapt to the times.